تطوير مادة البلاغة على ضوء المدخل التقابلي بجامعة الأزهري شيأنجور - Acep Hermawan (Jurnal Pendidikan Islam, 2012)
The research is an exploratory study to real condition STAI Cianjur students who find the difficulties whileBalagha by using the book which is intended for the native Arabs. Due to that reason, the researcherconsiders that it is necessary to design Balagha Curriculum which is easily understood by the students inIndonesia. The solution proposed is presenting the materials of Balagha contrastively: that is, by comparingthe similarities and differences with Indonesian Language system. The method used in this study is quasiexperimentalmethods. The experiments were carried out through giving pre-test and post-test to the students.Pre-test is to determine students’ prior understanding before the contrastive approach in learning Balagha isimplemented. Post-test is to determine students’ comprehension after the use of the approach. The result showsthat presenting Balagha materials through contrastive approach improves students’ learning outcomessignificantly. Thus, the development of Balagha teaching materials through contrastive approach can improvestudents’ understanding of Balagha materials.